Tildrakizumab in patients with metabolic syndrome: A novel approach (Canadian Dermatology Today, 2021)
Tildrakizumab is a high-affinity, humanized, IgG1 k antibody targeting interleukin 23 p19 to treat patients with chronic plaque psoriasis. The Food and Drug Administration (FDA) approved ILUMYATM (tildrakizumab-asmn) for the treatment of adults with moderate-to-severe plaque psoriasis who are candidates for systemic therapy or phototherapy in March 2018 and it has also been approved in Australia, Japan and numerous European countries. The approved recommended dosage of ILUMYATM in the United States is a subcutaneous injection of 100 mg at Weeks 0, 4, and every 12 weeks thereafter. In Canada, tildrakizumab has not yet been approved for the treatment of moderate-to-severe plaque psoriasis.This article presents a fictitious case study of a patient who may be a good candidate for tildrakizumab and provides an underlying rationale for the choice of tildrakizumab in this clinical scenario.A 39-year-old male presents to the office for a repeat visit for severe psoriasis. He has had psoriasis for 6 years and has failed topical therapy, and oral systemic agents. His past medical history is significant for obesity, hypertension, and impaired fasting glucose tolerance. His current medications include a multi-vitamin and an angiotensin receptor blocker. His family history is significant for obesity, hypertension, diabetes, and myocardial infarction. He travels quite frequently for work and, therefore is not able to commit to a phototherapy schedule. In choosing a biologic therapy, the new class of anti-IL23p19 agents have distinct clinical advantages that may be beneficial for this type of patient.